Understanding and improving safety in artisanal fishing: A safety-II approach in raft fishing - Carvalho, Ricardo José Matos de (2020)
Artisanal fishing with rafts is responsible for most of the Brazilian Northeastern region fishing production. Fishing is done in open sea, with very small boats in the unpredictable and often hostile maritime environment. Safety is achieved through the fishermen’s expertise to adjust their performance to cope with the demands and disturbances. Under this environment, safety should be improved by constraining the way people do things, based on traditional safety management principles or Safety I. This research describes a Safety II approach to improve raft fishing safety in a typical Brazilian beach community. Safety II main focus is on fishermen activities and strategies to construct safety during their fishing expeditions. The methods, following the action research iterative procedure, are workplace empirical studies to uncover knowledge, expertise, and artifacts that inform fishermen sensemaking and the Functional Resonance Analysis Method FRAM to model the fishing capture expeditions. Results indicated that the fishermen’s safety related trade-offs during fishing expeditions depends on their sensemaking, and to improve safety there is a need of a broader, systemic and continuous approach, involving not only objective measures and devices to inform and to support sensemaking for safer decisions, but also ways improve survival conditions of fishermen